Inoculation and co-inoculation of lettuce and arugula hydroponically influence nitrogen metabolism, plant growth, nutrient acquisition and photosynthesis - Oliveira, Carlos Eduardo da Silva; Sena Oliveira, Thaissa Julyanne Soares; Jalal, Arshad; Fernandes, Guilherme Carlos; Bastos, Andréa de Castro; da Silva, Marcelo Rinaldi; Sant’Ana, Gabriela Rodrigues; Aguilar, Jailson Vieira; de Camargos, Liliane Santos; Zoz, Tiago; Teixeira Filho, Marcelo Carvalho Minhoto (Frontiers in Plant Science, 2025)
The objective of this study was to investigate the effects of single and combined inoculations of A. brasilense, B. subtilis and P. fluorescens on lettuce and arugula grown in a hydroponic system. The study was carried out in a greenhouse and was designed in randomized blocks with five replications. The treatments consisted of inoculation with A. brasilense, B. subtilis and P. fluorescens and co-inoculation with A. brasilense + B. subtilis, A. brasilense + P. fluorescens, B. subtilis + P. fluorescens and A. brasilense + B. subtilis + P. fluorescens via nutrient solution. An increase in the length and fresh mass of the shoot and leaf chlorophyll concentrations of arugula and lettuce was observed under co-inoculations of A. brasilense + P. fluorescens and B. subtilis + P. fluorescens. Greater length, fresh mass and volume of the lettuce root system were observed under the co-inoculations of A. brasilense + B. subtilis, A. brasilense + P. fluorescens and B. subtilis + P. fluorescens in arugula under the inoculations of A. brasilense and A. brasilense + P. fluorescens. Greater nitrate reductase activity was detected in leaves, and lower nitrate accumulation was detected in lettuce and arugula under inoculations with A. brasilense, P. fluorescens and B. subtilis + P. fluorescens. The greatest accumulation of N, P, K, Ca and Mg in the lettuce shoot was obtained under inoculation with P. fluorescens, A. brasilense + P. fluorescens and B. subtilis + P. fluorescens. Co-inoculation with A. brasilense + P. fluorescens and B. subtilis + P. fluorescens was the most efficient combination for increasing the growth, nutrient acquisition and functioning of nitrogen metabolism in arugula lettuce plants.